Hispanics and Taxes: A Study in Inequality (Tufts Archival Research Center, 2007)
Report by the Labor Council for Latin American Advancement on Hispanics and federal taxes. Finds that the current tax system is not fair for Hispanics. Aims to show that the consumer excise tax and the payroll tax are "exceedingly unfair to Hispanics." Includes many tables comparing taxes paid by Hispanics and the lower income bracket versus those paid by caucasians and members of the upper class. Recommends curbing the payroll tax and consumer excise tax and increasing reliance on a fair income tax.